2013
DOI: 10.1016/j.wocn.2013.01.002
|View full text |Cite
|
Sign up to set email alerts
|

The uptake of spectral and temporal cues in vowel perception is rapidly influenced by context

Abstract: Speech perception is dependent on auditory information within phonemes such as spectral or temporal cues. The perception of those cues, however, is affected by auditory information in surrounding context (e.g., a fast context sentence can make a target vowel sound subjectively longer). In a two-by-two design the current experiments investigated when these different factors influence vowel perception. Dutch listeners categorized minimal word pairs such as /tɑk/–/taːk/ (“branch”–“task”) embedded in a context sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
166
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(186 citation statements)
references
References 52 publications
19
166
1
Order By: Relevance
“…Listeners would therefore be more likely to adapt to reduced /b/ when hearing it in its natural context. The suggestion that there are context-specific allophones is compatible with recent findings suggesting that the targets of recalibration may not be abstract phonemes (Mitterer, Scharenborg, & McQueen, 2013;Reinisch, Wozny, Mitterer, & Holt, 2014).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Listeners would therefore be more likely to adapt to reduced /b/ when hearing it in its natural context. The suggestion that there are context-specific allophones is compatible with recent findings suggesting that the targets of recalibration may not be abstract phonemes (Mitterer, Scharenborg, & McQueen, 2013;Reinisch, Wozny, Mitterer, & Holt, 2014).…”
Section: Discussionsupporting
confidence: 87%
“…Again, listeners do not only evaluate the raw incoming signal, they compute the incoming information (segment duration in this case) relative to talker-specific information (like speaking rate) available from the preceding context. Note, however, that these adjustment processes may not be tied to the perception of speaker identity, because evidence suggests that these normalizations occur at an early auditory level of processing (e.g., Reinisch & Sjerps, 2013;Sjerps, et al, 2011, for effects of preceding contexts; however, see Toscano & McMurray, 2012, for different effects of following contexts). In line with this assumption, normalization for speaking rate is speaker-independent, and speaker identity of the precursor has hardly any effects on normalization (Newman & Sawusch, 2009).…”
Section: Speaker-specific Learningmentioning
confidence: 99%
“…Diehl and Walsh (1989) found that the same nonspeech sound is perceived to be shorter before a long sound than before a short sound, and suggested that the findings of perceptual rate normalization studies may instead be attributed to general auditory contrast effects (see also Pisoni et al, 1983). Although Diehl and Walsh (1989) concerned the English /b/-/w/ contrast, if we applied the principle of auditory contrast effects to typical situations in perceptual VOT boundary experiments, the same VOT would be perceived to be shorter before a long segment (in the slow articulation condition) than before a short segment (in the fast articulation condition), which would produce a shift in the VOT category boundary in the direction reported by the perceptual rate normalization studies (see Reinisch and Sjerps [2013] for similar effects induced by temporally manipulating preceding speech contexts). In other words, the observed shifts in VOT category boundary locations in the previous perception experiments could have arisen from general auditory effects rather than speech rate normalization, which reflects listeners' knowledge of the temporal regularities of speech.…”
Section: Introductionmentioning
confidence: 99%
“…Through this process, they deal with the large variability in speaking rate during speech perception. That is, following a fast context sentence, a given sound is interpreted as longer than when it follows a slow context sentence (e.g., Ainsworth, 1972Ainsworth, , 1974Allen & Miller, 2001;Dilley & Pitt, 2010;Kidd, 1989;Miller, 1981Miller, , 1987Miller & Dexter, 1988;Newman & Sawusch, 2009;Reinisch, Jesse, & McQueen, 2011;Reinisch & Sjerps, 2013;Summerfield, 1981). For example, the wordinitial stop voicing contrast in English (e.g., /g/ vs. /k/) is mainly cued by temporal properties, namely duration of voice onset time (VOT).…”
mentioning
confidence: 99%